New data on the number of northern fur seal ( Callorhinus ursinus), Steller sea lion ( Eumetopias jubatus), and spotted seal ( Phoca largha) at Tyuleny Island (Okhotsk Sea) - Alexey E. Kuzin (Известия ТИНРО)
The latest data on abundance and distribution of northern fur seal ( Callorhinus ursinus ), Steller sea lion ( Eumetopias jubatus ), and spotted seal ( Phoca largha ) at Tyuleny Island (Okhotsk Sea) are presented. The total counted number of fur seals was 115 thousand in June-July of 2013, including 5.0 thousand of bulls, 30.3 thousand of females, and 34.7 thousand of pups (31.5 thousand alive and 3.2 thousand dead). Decreasing of the females and pups number is observed during the last 4 years - they became lesser in 18.0 % or 4.5 % per year. The counted number of Steller sea lions was 1879 adults (including 119 bulls, and 1390 females, 68.5 % of them gave birth) and 890 pups. The reproductive group of Steller sea lion increases its abundance on the island due to numerous immigrants. Abundance of spotted seal was very various seasonally and even daily, its highest counted number was 162 individuals.